Determining a diagnostic cut-off on the Teate Depression Inventory - Balsamo M (Dove Medical Press, 2014)
Michela Balsamo, Aristide SagginoDepartment of Psychological Sciences, Humanities and Territory, G. d’Annunzio University of Chieti-Pescara, Chieti, ItalyAbstract: A small but growing body of literature suggests that the Teate Depression Inventory (TDI) may be an “objective” measure of depression compared with other commonly used scales. Furthermore, the TDI has strong psychometric properties in both clinical and nonclinical samples. The present study aimed to extend the use of TDI by identifying cut-off scores that could differentiate varying levels of depression severity in a group of clinically diagnosed depression disorder patients (N=125). Three receiver operating characteristic curve analyses indicated cut-off scores of 21 (sensitivity =0.86, specificity =0.94, and classification accuracy =0.90); 36 (sensitivity =0.84, specificity =0.96, and classification accuracy =0.92); and 50 (sensitivity =0.81, specificity =0.93, and classification accuracy =0.90), for minimal, mild, moderate, and severe depression, respectively. Results suggest that the TDI measures depression severity across a broad range with high test accuracy and may be appropriately used to screen for depression.Keywords: major depression, ROC curve, self-report scales, Rasch analysis, depression screening